PROBLEMS OF THE RATIONAL USE OF PEDIGREE RESOURCES IN POLTAVA REGION - Волощук, В. М.; Замикула, В. В.; Березовський, М. Д.; Підтереба, О. І. (Scientific Progress & Innovations, 2013)
The questions of the cause of ineffective work of pedigree enterprises, their presence and necessary number for effective annual production of 300 000 heads are examined in the article. The data, which show the dependence of a structure of selective industrial pyramid from the level of technological indexes, are given. The prognosis of a change of the structure of industrial pyramid is carried out by the application of information systems and the optimal variant, which will be applied at planning of annual amounts of the production of pig products on the three breads base, is chosen.